DEVELOPMENT OF THE GILI MANDANGIN TOURIST AREA BASED ON RESILIENCE, THROUGH SMART CITY METHODS AND CONNECTIVITY - Yogi Fitrianto; Retno Hastijanti; Darmansjah Tjahja Prakasa (International Conference of Innovation and Community Engagement, 2024)
Gili Mandangin, a small island in Sampang Regency, Madura, has great potential to develop into an attractive tourist destination with its natural beauty and cultural richness [1] However, challenges such as limited infrastructure, vulnerability to climate change, and low connectivity levels hinder the maximization of that potential. This research aims to formulate a resilience development strategy based on tourism in Gili Mandangin by applying the Smart City concept [2] and the enhancement of connectivity among stakeholders. The research method used involves qualitative analysis through literature studies, interviews with relevant parties, and field observations to understand the conditions and challenges faced. The Smart City approach [2] is proposed as a solution to leverage technology in resource management, improve information access, and enhance system integration in the tourism sector. In addition, the improvement of connectivity [3]. among local communities, industry players, and the government is seen as an important step to create a sustainable and resilient tourism ecosystem. The implementation of Smart City in Gili Mandangin can strengthen tourism resilience by optimizing destination management, improving public service efficiency, and expanding market access for local products [4]. Better connectivity enables effective coordination in facing economic and environmental challenges, as well as encouraging community participation in the development of `sustainable tourism. This strategy is expected to enhance the competitiveness of Gili Mandangin as an adaptive and innovative tourist destination in the digital era.